From Destination to Transit Stop: Syrian Migrants Revising Their Dreams in Japan - al-Masri, Mohammed (Border Crossing, 2025)
Migration to unusual destinations, including Japan, has become a significant phenomenon for hundreds of Syrian (forced) migrants who live in Syria’s neighboring countries. Unable to repatriate while facing unprecedented social and economic challenges in their countries of refuge, resettlement through safer routes and less competitive pathways to better destinations has become a viable option for many. Japan, due to its geographical distance and cultural differences, was an unusual destination for Syrians. Over the course of thirteen years, migration to Japan shifted from a historically lesser-known path, with 188 Syrians residing in the country, to a more popular sanctuary, hosting nearly 1,500 in 2024. This study aims to investigate the socio-economic factors that have led Japan to become a transit stop for many Syrians who had different plans before coming. Most of the existing research focuses on immobility in developing countries of refuge, people’s inability to leave their country of origin, asylum seekers stranded in ‘transit’ countries, in addition to examining repatriation barriers. This study investigates a unique case where migrants are living in a developed country presumed to be their final destination, only to realize it has become another phase in their journey. Due to Japan’s highly-esteemed reputation in the Arab world and the perceived image of life in Japan, Syrians had highly expectations assuming challenges would be considerably minor. Many decided to leave because of these unmet expectations, despite the presumed exceptional quality of life and the convenience of the country.